Ingol, ent-atisane, and stachane-type diterpenoids from Euphorbia deightonii with multidrug resistance reversing activity. (December 2022) - Saidu, Muhammad Bello; Kúsz, Norbert; Berkecz, Róbert; Rácz, Bálint; Spengler, Gabriella; Hohmann, Judit; Rédei, Dóra
Abstract: Nine previously undescribed ingol-type diterpenoid polyesters with eighteen known ingol esters, two ent -atisane, and one stachane diterpenoid were isolated from the methanol extract of Euphorbia deightonii Croizat. The structures were established by extensive spectroscopic analysis involving 1D ( 1 H, 13 C J-modulation) and 2D NMR experiments, HRESIMS measurements, and the comparison of the spectroscopic data with reported literature values. The cytotoxic concentrations of 13 isolated compounds were determined, and the compounds were investigated for multidrug resistance modulating activity on an L5178 mouse lymphoma cell line using a rhodamin 123 accumulation assay. Six ingol esters demonstrated the significant inhibition of P-glycoprotein, while the two ent -atisane diterpenoids were found to be inactive. The measured activities allowed to establish some structure–activity relationships. Notably, lower and higher-type diterpenoids simultaneously occurred in E. deightonii . Graphical abstract: Thirty diterpenes including nine undescribed ingol-type polyesters were isolated from Euphorbia deightonii . The cytotoxic concentrations of thirteen diterpenes were determined, and the compounds were investigated for multidrug resistance modulating activity. Image 1 Highlights: Nine unreported diterpenoids from Euphorbia deightonii Crozat. 30 diterpenes of three different types: ingol, ent -atisane, and stachane. Some ingol esters inhibit MDR efflux pump in cancer cells. Salicylic acid esterifies one of the Euphorbia diterpenes.